Canon photography workshop - Multicom (Firm).; Big Wig Productions; Kyanon Kabushiki Kaisha (Seattle, Wash. Multicom Big Wig Productions, 1996)
Step by step guide to taking better photos with any camera. Practice different camera angles, lenses, film speed, filters, exposures, lighting on location with the experts.
Title and ed. statement from disc surface.
"CD vision."
"XPBX101"--Container.
System requirements for Windows: Multimedia PC, 33 MHz 486DX or better; 8MB RAM; DOS 5.0; Windows 3.1+ or Windows 95; 2X CD-ROM drive; SVGA display at 256 colors; MPC audio board; mouse.
System requirements for Macintosh: 68030 processor or better; 8MB physical RAM with 4MB free; System 7.1; 13" color Macintosh monitor with 256 colors; 2X CD-ROM drive; QuickTime 2.0 or higher.
Keywords: Photography -- Handbooks, manuals, etc